Specific character and structural features of human identity - Nurmanbetova, Jamilya N. (Opción, 2019)
This article is devoted to the present-day theoretical discourse on human identity and its architectonics via a number of humanitarian research methods, such as source analysis of the literature on the subject. Deep theoretical analysis showed that all types of identity (both in objective reality and in the subjective world) logically included in hierarchical structures, were always axiologically determined and corresponded to fixed cultural values. As a conclusion, the ability to relate the self-esteem to social assessment in a proper way requires significant development of thought and may indicate the high potential of identity development